1976
DOI: 10.1210/endo-98-4-1014
|View full text |Cite
|
Sign up to set email alerts
|

Development of Insulin and Glucagon Binding and the Adenylate Cyclase Response in Liver Membranes of the Prenatal, Postnatal, and Adult Rat: Evidence of Glucagon “Resistance”

Abstract: Although plasma glucagon levels in the rat fetus are in the adult range, hepatic glycogen is present in far greater abundance in the fetus than in the adult. To explain this paradox, adenylate cyclase response to glucagon was studied in partially purified membranes of rat livers obtained throughout perinatal life and at 3 months of age. The adenylate cyclase response to glucagon (10(-9) M) was only 7% of the adult response at day 15 of fetal life and 20% on the 21st day. No until after the 30th day postpartum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

1979
1979
1994
1994

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(45 citation statements)
references
References 0 publications
0
45
0
Order By: Relevance
“…In the rat, Blazquez et al have shown that the adenylate cyclase response to glucagon rises steadily throughout prenatal life and does not reach adult levels until day 30 of post-natal life. This increase in glucagon sensitivity in the older rats was directly correlated with an increase in glucagon binding to hepatocytes [32]. In contrast, Lockwood et al observed a decline in glucagon binding during aging in rat adipocytes [33], but not hepatocytes [34].…”
Section: Discussionmentioning
confidence: 90%
“…In the rat, Blazquez et al have shown that the adenylate cyclase response to glucagon rises steadily throughout prenatal life and does not reach adult levels until day 30 of post-natal life. This increase in glucagon sensitivity in the older rats was directly correlated with an increase in glucagon binding to hepatocytes [32]. In contrast, Lockwood et al observed a decline in glucagon binding during aging in rat adipocytes [33], but not hepatocytes [34].…”
Section: Discussionmentioning
confidence: 90%
“…In man, Rosenfeld et al (6) reported that the number of somatomedin receptor sites on mononuclear cells was greater in neonates than in adults. Insulin receptors have been reported in fetal pig (3), rat (7,8), rabbit, and guinea pig (8). In man, insulin binding to mononuclear cells is higher in newborns than in adults (9) and in preterm as compared with term infants (10).…”
Section: Introductionmentioning
confidence: 99%
“…As we have demonstrated, although a-adrenergic receptors are present in the newborn hepatocyte in concentrations even greater than 0-adrenergic receptors, their stimulation does not lead to a rise in glycogen phosphorylase activity. In addition sensitivity of the liver to glucagon, the other major hormone involved in glucose homeostasis, is apparently less in the newborn than in the adult (27).…”
Section: Resultsmentioning
confidence: 99%